The physiology of vegetable crops - Wien, Hans Christian, 1940-; Stützel, Hartmut, 1954- (CAB International, 2020)
"Completely updated and revised, this bestselling book continues to explain the growth and developmental processes involved in the formation of vegetables. Since the publication of the successful first edition significant discoveries, particularly in the area of molecular biology, have deepened and broadened our knowledge and understanding of these processes. This new edition brings the topic up-to-date and is presented over two sections: the first provides general knowledge on germination, transplanting, flowering, the effects of stress and modelling, whilst the second section details the physiology of specific crops or crop groups. The second edition of The Physiology of Vegetable Crops: · contains two new chapters looking at stress effects on vegetable crops with a particular emphasis on climate change and models of vegetable growth and development · is fully updated to reflect recent discoveries and the advent of new production techniques such as growing in artificial environments · provides enhanced understanding of the growth and function of more than 21 vegetable crops · is heavily illustrated and published in full colour throughout With contributions from renowned international experts, this is an essential resource for horticultural researchers and extension educators and consultants, as well as a reference for students and professors in vegetable production, plant breeding, entomology and plant pathology"--